Research Highlight, 75 Years of RILEM: Materials & Structures - Constantinides, Georgios (My University, 2026)
Our 2003 Materials & Structures paper (https://link.springer.com/article/10.1007%2FBF02479557): Constantinides G., Ulm F.-J., van Vliet K.J., `On the use of nanoindentation for cementitious materials', Materials and Structures (Special issue of Concrete Science and Engineering), Vol. 36 (205), 191-196, April 2003. has been selected to be highlighted as one of the most significant articles that have been published in the journal throughout its history, as part of the 75-year anniversary celebration of RILEM. Link to the commemerative article: https://link.springer.com/article/10.1617/s11527-021-01870-z
Keywords: Sciences